Clinical effectiveness and implementation outcomes of pMDI-to-DPI switch in children between 5 and 12 years of age: a scoping review protocol - Nick Sevdalis; Nick Watts; Amanda Zain; Alston Z Y Ng; Inez Yeo (BMJ Open)
Introduction Inhalers are critical in asthma treatment, and inappropriate inhaler use leads to poor asthma outcomes. In adults and adolescents, dry powder inhalers (DPIs) are safe and effective alternatives to mainstay pressurised metered dose inhalers and could bridge the asthma care gap while also reducing the environmental burden of asthma care. Despite being licensed for use in ages 5 years old and older, the evidence for clinical effectiveness is less clear for patients between ages 5 and 12 years. This protocol describes a scoping review. The primary aim of the review is to identify and synthesise evidence on the clinical effectiveness of DPI use in children aged 5–12 years old with asthma and other wheezing conditions. The secondary aim of the review is to outline the implementation strategies and outcomes supporting the prescribing or switching to DPIs in children.Methods and analysis We will conduct a systematic and comprehensive literature search across four electronic databases (Medline, Embase, Cochrane Library and CINAHL) and grey literature. Screening and data extraction will be done independently by two review authors with discrepancies resolved through consensus. Data will be extracted and charted by two independent reviewers, then presented diagrammatically or tabulated with an accompanying narrative summary.Ethics and dissemination Ethical approval was not required for this study as it is a scoping review. The results of this scoping review will be submitted to a peer-reviewed scientific journal for publication.